Paul and the Heritage of Israel: Paul's Claim upon Israel's Legacy in Luke and Acts in the Light of the Pauline Letters - Moessner, David P. (Library of New Testament Studies, The, 2012)
As a sequel to the hugely successful Jesus and the Heritage of Israel this book brings together fourteen internationally acclaimed scholars in antiquities studies and experts on Paul and Luke. The contributors provoke new approaches to the troubled relation of the Lukan Paul by re-configuring the figure and impact of Paul upon nascent Christianity, with the two leading questions as a driving force. First, Who is Israel and the church for Luke and Lukes Paul and secondly Who is Jesus of Nazareth and who is Paul in relation to both? The contributors provide challenging new perspectives on approa